EFL STUDENTS’ PERCEPTION ON THE USE GOOGLE CLASSROOM IN ENGLISH CLASS - Muhalida Zia Ibhar (PROJECT (Professional Journal of English Education), 2023)
Recent years have seen an unprecedented impact of technological advancements on all facets of our humanity and society, including business operations procedures. A collection of online productivity tools for teachers and students engaged in online learning and collaboration, Google Classroom is a component of Google Apps for Education (GAFE). The study aims to investigate students' perceptions of using Google Classroom in English class, Public Administration at STIA Lancang Kuning Dumai, Indonesia. The participant of this research was 40 students enrolled in English class. The questionnaire used a Likert scale with two options that ranged from "agree" to "disagree." 7 questionnaire items were used to answer the research questions. The results of the study show that students are enthusiastic about using Google Classroom in essay writing classes. It implies that Google Classroom exercises improve students' writing. Keywords: EFL Students; E-Learning, English Class; Google Classroom; ICT